Unexplained recurring high mortality of southern right whale calves (Eubalaena australis) at Península Valdés, Argentina - Rowntree, Victoria J.; Uhart, Marcela M.; Sironi, Mariano; Chirife, Andrea; Di Martino, Matias; la Sala, Luciano Francisco; Musmeci, Luciana Raquel; Mohamed, Nadia; Andrejuk, Julian; Mcaloose, Denise; Sala, Juan Emilio; Carribero, Alejandro; et al. (Marine Ecology Progress Series)
Hundreds of southern right whale calves Eubalaena australis died on their calving ground at Península Valdés, Argentina from 2003 through 2011. During this period, the number of dead calves increased at a much greater rate than that of living calves over the preceding 32 yr, and with greater inter-annual variation. High mortality events occurred late in the calving seasons of 2005 and 2007, early in the seasons of 2008 and 2009, and were equally divided between early and late in 2010 and 2011. Calves that died late in the seasons of 2005 and 2007 were at least a meter longer (mean 7.3 m) than newborns, indicating that they had grown and presumably were healthy before dying. An unusual number of large calves (>6 m) died early in the seasons of 2008 and 2009, suggesting that a population-wide process (e.g. nutritional stress) affected many mothers including older, larger mothers that tend to give birth to larger calves early in the season. Many tissue samples have been collected and analyzed, but no consistent lesions, pathologic processes or elevated levels of algal biotoxins have been identified to explain these recent mortality events. Here, we document the high mortality events, place them in historical context and describe ongoing efforts to identify their causes. As of 2010, the southern right whale sub-population that calves off Península Valdés was estimated to be less than 20% of its initial size before whaling; the ongoing high mortality of calves will significantly affect its recovery. Fil: Rowntree, Victoria J. University Of Utah; Estados Unidos. Programa de Monitoreo Sanitario Ballena Franca Austral; Argentina. Whale Conservation Institute/Ocean Alliance; Estados Unidos Fil: Uhart, Marcela M. University Of California; Estados Unidos. Programa de Monitoreo Sanitario Ballena Franca Austral; Argentina Fil: Sironi, Mariano. Programa de Monitoreo Sanitario Ballena Franca Austral; Argentina. Instituto de Conservación de Ballenas; Argentina Fil: Chirife, Andrea. Programa de Monitoreo Sanitario ...